2022
DOI: 10.22271/oral.2022.v8.i1g.1460
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of colour stability and surface roughness of three CAD/CAM materials (IPS e.max, Vita Enamic, and PEEK) after immersion in two beverage solutions: An in vitro study

Abstract: To evaluate the colour stability and surface roughness of 3 different CAD/CAM materials (IPS e.max, Vita Enamic, and PEEK) after immersion in two beverage solutions (Coffee, Coca-Cola). Methodology: Samples from a lithium disilicate glass-ceramic (IPS e.max CAD), a hybrid ceramic (Vita Enamic), and PEEK (BioHPP) were evaluated for colour change and surface roughness under immersion in two beverage solutions (Coffee, Coca-Cola). A total of 30 samples were prepared n=10 each. Spectrophotometer analysis was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 34 publications
2
9
1
Order By: Relevance
“…The color stability of the restoration is the most sought-after esthetic property. The degree of discoloration depends mainly on the material composition, solution type and exposure time [ 7 ]. In studies regarding the ceramic color stability, mostly tea, cola, and coffee were used as coloring agents [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The color stability of the restoration is the most sought-after esthetic property. The degree of discoloration depends mainly on the material composition, solution type and exposure time [ 7 ]. In studies regarding the ceramic color stability, mostly tea, cola, and coffee were used as coloring agents [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Green tea, coffee and Coca-Cola are the most regularly consumed acidic drinks in daily life. Green tea and coffee have a pH of 5.8 and consist of caffeine, tannates, citrates and chlorogenic acid, whereas Coca-Cola has a pH of 2.5 and is made up of phosphates, carbonated water, and caramel [ 47 , 48 ]. Staining of ceramics caused by these low-pH acidified beverages may compromise the cosmetic outcome [ 49 51 ], thereby reducing durability of the material, resulting in roughness, abrasion, and subsequent staining of teeth, ultimately causing patient dissatisfaction [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies evaluated the color porcelain materials stability concerning the surface texture, concluding that accurate polishing procedures could create smooth ceramic surfaces similar to glazed surfaces [ 51 , 53 ]. Glazing has been found to produce smoother surfaces than glass ceramic polishing [ 48 ]. Manufacturers also advocate glazing or polishing to improve the aesthetics of lithium disilicate [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on a previous study Alsilani et al 35 , it was found that a sample size of 18 per group possess an 80% power to detect an increase of 0.50 with a significance level (alpha) of 0.05 (two-tailed) and 95% confidence intervals. In 80% the power of those experiments, the P value will be less than 0.05 (two-tailed) so the results are to be considered "significant statistically".…”
Section: A Study Design and Sample Estimationmentioning
confidence: 99%